FACTORS CONTROLLING RESERVOIR DISTRIBUTION IN THE SOUTH ERAWAN GRABEN, PATTANI BASIN, GULF OF THAILAND - Paiboon, Pakawat (Bulletin of Earth Sciences of Thailand, 2021)
The reservoirs in South Erawan Field, Pattani Basin, Gulf of Thailand are mostly thin sands where distribution is difficult to predict due to rapid vertical and lateral facies changes. Sand distribution may controlled by 1) faults or 2) sediment supply. Fault control was investigated in this study for stratigraphic units 3 and 4 which are the main hydrocarbon producing intervals. The study analysed 1) fault movement using isochore maps and expansion index, and 2) sand distribution using seismic attributes. Both analyses integrated a 3D seismic volume with all wells data in the study area. Expansion Indices are high at the bounding faults, indicating a high relative amount of fault movement, and decrease to the graben center faults. Upper stratigraphic unit 3 has the highest relative amount of fault movement. Sand distribution analysis in all intervals indicates that there is no fault control on sand distribution because sand spreads across faults and no sand is limited to a specific fault zone. Therefore, sand distribution probably was controlled by sediment supply as sedimentation rate was higher than the rate of fault movement.